A New Design Using Metal Wire Brushes as the Current Collector and Catalyst Carrier for Internal Reforming of Micro-Tubular SOFCs. Issue 10 (12th October 2021) - Shi, J.; Fan, J.; Wang, Y.; Shi, Y.; Cai, N.
Abstract : In this study, a novel current collecting method of inserting metal wire brushes into anode-supported micro-tubular solid oxide fuel cells (MT-SOFCs) was designed and demonstrated. The proposed design enabled a tight and stable contact between the wires and the interior surface of the anode, which led to good performance of the SOFC. Different metal wire materials were utilized, and copper–zinc wire brushes (CZWBs) showed better performance than stainless steel wire brushes (SSWBs). The MT-SOFCs using CZWBs achieved a maximum power density of 290 mW cm −2 and a minimum ohmic resistance of 0.66 Ω∙cm 2 at 700 °C in a hydrogen stream. The brush size was shown to have little effect on the ohmic resistance. A long-term discharge test (108 h) was also carried out. The feasibility of using metal wire brushes as internal reforming catalyst carriers was experimentally verified. The SSWBs loaded with Pt catalyst could realize effective reforming of methane, demonstrating the potential of the proposed design to use hydrocarbon fuels for power generation.